Combinatorial library of primaryalkylammonium dicarboxylate gelators: a supramolecular synthon approach - Sahoo, Pathik; Adarsh, N. N.; Chacko, George E.; Raghavan, Srinivasa R.; Puranik, Vedavati G.; Dastidar, Parthasarathi (Langmuir, 2009)
Following the supramolecular synthon approach, a combinatorial library comprising 35 organic salts derived from 7 dicarboxylic acids (malonic, succinic-, adipic, L-tartaric-, maleic-, phthalic-, and isophthalicacid) and 5 primaryalkyl amines Me-(CH2)(n)-NH2 (n = 11 - 15) was prepared and scanned for gelation. About 66% of the salts in the combinatorial library were found to show moderate to good gelling ability in various polar and nonpolar solvents including commercial fuels such as petrol. The majority of the salts having a rigid, unsaturated anionic backbone (maleate, phthalate, and isophthalate) did not show gelation; only the corresponding hexadecylammonium salts showed gelation. Some of the representative gels were characterized by rheology, small-angle neutron scattering (SANS), optical microscopy (OM), and scanning electron microscopy (SEM). Single-crystal structures of two gelator and two nongelator salts were also discussed in the context of supramolecular synthon and structure-property correlation.